1995
DOI: 10.1111/j.1430-9134.1995.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Choice Among Regulatory Plans in the U.S. Telecommunications Industry

Abstract: We investigate why different states in the United States choose different regulatory plans in their telecommunications industry. We present a simple theoretical model and an empirical analysis of the issue. We find that a state is more likely to replace rate‐of‐return regulation with incentive regulation when: (1) residential basic local service rates have historically been relatively high; (2) allowed earnings under rate‐of‐return regulation in the state have been either particularly high or particularly low;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…This is also in line with the …dnings by Teske [1991aTeske [ , 1991b and Donald andSappington [1995, 1997], who did not …nd elected regulators to signi…cally impact regulatory decisions.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…This is also in line with the …dnings by Teske [1991aTeske [ , 1991b and Donald andSappington [1995, 1997], who did not …nd elected regulators to signi…cally impact regulatory decisions.…”
supporting
confidence: 71%
“…First, in many states the regulatory ban was imposed at the legislative level, therefore the governor's political orientation should account for its speci…c preferences in the regulatory policy. Second, the political orientartion of the party in power can be seen, according to Donald andSappington [1995, 1997], as a measure of the political costs of choosing a regulated regime for the mobile industry. Third, one may want to control for political variables because the 18 As long as the consumer surplus is included in the welfare function maximized by the regulator, the coe¢cient ® 1 cannot be negative.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Policy makers may use a number of tools to favor the entrants. Hence the policy variable, measured with an entry barriers index, will describe both the elimination of regulatory barriers to entry, and cases where regulation actually favors entry 10 (a higher value of the index will indicate 9 See Donald and Sappington (1995). 10 Elimination of regulatory barriers is usually associated to the term "deregulation", whereas favouring entrants through regulation could be called "asymetric regulation."…”
Section: Set Up and Hypothesesmentioning
confidence: 99%
“…Specifically, , Donald and Sappington (1995), and Donald and Sappington (1997) found that incentive regulation like price-cap regulation tends to have a bigger impact on investment in telecommunications than rate-of-return regulation. However, as Berg and Foreman (1996) and Kridel et al (1996) warn, the links between the regulatory regime and telco performance are complex, so studies need to avoid pitfalls and must be carefully interpreted.…”
mentioning
confidence: 99%